Popularitas Tari Lengger Lanang di Kalangan Anak Muda Banyumas - Sherly Dwi Caroline Enhar (TAMUMATRA, 2024)
The Banyumas lengger dance has become an integral part of the communal life of the Banyumas people because of its rapid development. One example of this dance variation is the Banyumas Lengger Lanang dance. Cross gender is a role or characteristic that is different from a person's gender identity, which is also known as cross gender. Nowadays, the Lengger Lanang dance is still very popular because every year there are always successors or generations who continue to continue the Lengger Lanang dance culture. The aim of this researcher is to reveal the popularity or existence of the Lengger Lanang dance among young people today as well as the enthusiasm of young people to preserve the Lengger Lanang dance culture in Banyumas. This research uses descriptive qualitative methods. In descriptive qualitative research, data analysis is carried out based on observed symptoms, which are not always represented by numbers or coefficients that connect variables. The research subject is the impact of the lengger house on young people's interest in preserving the Banyumas lengger dance in Banyumas district. This research uses researchers as the main instrument, supported by writing tools such as books, pens, voice recorders and other assistive devices. Data collection techniques include literature study, observation, interviews and documentation. Data analysis steps include data reduction, data presentation, and data conclusion. The research results show that the popularity of Lengger Lanang continues to increase among today's young generation.